2013
DOI: 10.7726/aja.2013.1002
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and Factors Associated with Death in Autism Spectrum Disorders - a Review

Abstract: The purpose of this review is to provide information on mortality and factors associated with death in people with autism spectrum disorder (ASD). A review of the published systematic mortality studies suggest that the observed number of deaths is nearly three times higher in populations with ASD than in the general population. Research into risk factors associated with survival in people with ASD is limited, and no studies have controlled for changes in these factors over time. The most important risk factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 32 publications
(47 reference statements)
0
7
0
Order By: Relevance
“…The present study found no support for an association between mortality risk and sociodemographic factors of remoteness and socioeconomic status. Female gender has often been associated with higher mortality rates for those on the autism spectrum (Mouridsen, ; Woolfenden et al, ). Similarly, the univariate results indicate a significant association between being female and heightened mortality risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study found no support for an association between mortality risk and sociodemographic factors of remoteness and socioeconomic status. Female gender has often been associated with higher mortality rates for those on the autism spectrum (Mouridsen, ; Woolfenden et al, ). Similarly, the univariate results indicate a significant association between being female and heightened mortality risk.…”
Section: Discussionmentioning
confidence: 99%
“…Female gender, comorbid epilepsy, and the presence and degree of ID have been associated with higher mortality rates in those on the autism spectrum (Gillberg, Billstedt, Sundh, & Gillberg, ; Hirvikoski et al, ; Mouridsen, Bronnum‐Hansen, Rich, & Isager, ; Shavelle, Strauss, & Pickett, ). Studies also suggest that mortality for those on the spectrum is associated with concurrent ID and its related medical comorbidities, such as cardiovascular disease and other mental/behavioral disorders, rather than an outcome of autism spectrum disorder (ASD) itself (Bilder et al, ; Mouridsen, ; Schendel et al, ). Alternatively, co‐occurrence between ASD and other factors such as social or financial disadvantage (Henninger & Taylor, ; Howlin, ), poor access to or insufficient health services (Nicolaidis et al, ), inadequate or under‐skilled health workforce (Zerbo, Massolo, Qian, & Croen, ), and polypharmacy (Lake, Balogh, & Lunsky, ) may contribute to excess mortality.…”
Section: Introductionmentioning
confidence: 99%
“…As a possible consequence of underutilization of healthcare resources leading to unmet needs, an increased overall mortality has been observed in the ASD population (39)(40)(41). This is associated with complications related to different comorbidities including suicide, accidental death resulting from unsafe behaviors, use of supplemental medications such as atypical antipsychotics, poor nutrition, and insufficient/inappropriate use of healthcare resources (42)(43)(44)(45). Specifically, the odds ratio of death from a neoplasm was estimated to be close to double in individuals with ASD (1.83 in females, 1.79 in males) when compared than non-ASD controls (41).…”
Section: Healthcare and Cancer Care For Individuals With Asdmentioning
confidence: 99%
“…High profile incidents including drownings and traffic accidents prompted calls for more research focused on understanding and preventing elopement (The Autism Wandering Awareness Alerts Response and Education (AWAARE) Collaboration; McIlwain and Fournier 2012). In parallel, research on the causes of elevated mortality among individuals with ASD (Gillberg et al 2010;Guan and Li 2017;Mouridsen 2013;Schendel et al 2016), including one study documenting a 40-fold increased risk of drowning for these individuals, (Guan and Li 2017), pointed toward elopement as a potentially important modifiable risk factor for individuals with ASD.…”
Section: Current Knowledgementioning
confidence: 99%